Locus of Control Mediates Impulsive Buying at Coffee Shops in Kendari City A Conceptual Paper - Fahri, Muhammad Afdhal; Widodo, Arry; Rubiyanti, Nurafni; Silvianita, Anita (East Asian Journal of Multidisciplinary Research, 2025)
This study focuses on exploring impulsive buying behavior among consumers, particularly in the context of the rapid growth of the coffee shop industry. This Conceptual Paper aims to understand the factors that influence this behavior, also integrates Locus of Control as an intervening variable, in order to analyze how these psychological as factors mediate the relationship between FoMO, peer groups, and impulsive buying tendencies. Using a quantitative approach and causality design, this study examines the relationship between the independent variables (FoMO and peer groups) and the dependent variable (impulse buying), focusing on the mediation mechanism played by Locus of Control. The study aims to benefit Kendari City's coffee shop industry by offering insights to develop marketing strategies that align with consumer behavior, ultimately enhancing customer loyalty.